Development of a heterologous human CYP2C9-NADPH P450 reductase system: An in vitro enzyme system for drug metabolism study / Riza Afzan Asri - Asri, Riza Afzan (2010)
A heterologous system that enables rapid screening of the principal routes of metabolism of drugs, herbs, food and new chemical entities (NCE) would be of enormous benefit in research and drug development. Cytochrome P450 (CYP) 2C9 is one of the principal enzymes involved in the metabolism of many drugs such as phenytoin, warfarin, tolbutamide, celecoxib, fluoxetine and losartan. However, to date its roles in the clearance of other compounds such as local herbs Eurycoma longifolia Jack (Tongkat Ali) have not been reported. An inMtro heterologous enzyme system was developed using E. coli (DH5a) to study the metabolism of these compounds. Recombinant CYP2C9 and NADPH-Cytochrome P450 reductase were co-expressed in separate but compatible plasmid to generate an active in-vitro drug metabolizing system. The yield of the protein expressed was at the optimum level when the culture were incubated at 30°C and harvested after 24 hour. Immunoblotting demonstrated the presence of both CYP2C9 and reductase protein with sizes approximately 55 kDa and 80 kDa respectively. The kinetic activity of the enzyme was characterized using fluorescent base Vivid® CYP450 Screening Kit. Incubation of enzymes with different concentration of BOMCC substrate was done to determine the kinetic parameters (V max = 64.1 nM, Km = 99.1 pM). Assay between CYP2C9-Eurycoma longifolia Jack(Tongkat Ali) was carried out to study the possibility of the inhibition effect of Tongkat Ali towards the enzyme. Presence of 20 pg and 50 pg Tongkat Ali in the reaction showed reduced enzyme activity. Higher concentration of Tongkat Ali gave higher inhibition, thus lowering the velocity of enzyme in which its k, value is 5408.9 pM. The result of this study contributes in enhancing the drug-herb interaction database profile on the metabolism pathway and inhibitory effects of local herbs towards CYP2C9.